Tahwīl at-Taʽlīm: Tahdiyāt Manhaj Merdeka fī Taʽlīm al-Lughah al-ʽArabiyah bi Madrasah al-Islāmiyah al-Hukūmiyah 2 Panyabungan - Tauhid (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2024)
Education plays a crucial role in national development, and the effectiveness of an educational system heavily relies on the curriculum implemented. The Merdeka Curriculum was introduced in Indonesia as an effort to provide flexibility in learning; however its implementation faces various challenges, particularly in the instruction of the Arabic language at MAN 2 Panyabungan. This study aims to explore and analyze the challenges encountered in the application of the Merdeka Curriculum within the context of Arabic language learning. The research employs a case study methodology, with data collected through in-depth interviews with teachers, school principals, and students, as well as direct observations in the classroom. Documents such as lesson plans (RPP) and teaching materials were also analyzed to gain a more comprehensive understanding. The findings indicate several obstacles, including teachers' understanding of the new curriculum, infrastructure readiness, and student participation in the learning process. These results highlight the need for better strategies to align theory with practice. Based on the research findings, it is recommended that the school and other stakeholders develop training programs for teachers and enhance supporting infrastructure to address the challenges in implementing the Merdeka Curriculum in Arabic language education. This study aims to provide in-depth and practical insights for the improvement of educational practices